1988
DOI: 10.1210/endo-123-3-1405
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Gonadal Steroids on Somatotroph Function in the Rat: Analysis by the Reverse Hemolytic Plaque Assay*

Abstract: The mechanism by which gonadal steroids modulate GH secretion is not known. We have used the reverse hemolytic plaque assay to examine whether gonadal steroid-induced modulation of GH secretion is effected by changes in the population of somatotrophs and/or alterations in their secretory properties. Two groups of Sprague-Dawley rats were studied: group 1 (n = 6) comprised male (M), castrate (Cx), and testosterone-replaced castrate male (Cx + T) rats and group 2 (n = 5) consisted of male (M), female (F), and 17… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
31
1

Year Published

1990
1990
2001
2001

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(39 citation statements)
references
References 0 publications
7
31
1
Order By: Relevance
“…Using the thymidine kinase obliteration system, Borrelli et al [3] reported that both GH cells and PRL cells derive from a common GH-expressing stem GH cell, which terminally differentiates into GH and PRL cell populations in transgenic mice. These findings support a possible transformation of GH cells into PRL cells, with MS cells acting as an intermediate cell in swine adenohypophysis as previously described in the adenohypophysis of rats [5,13,26,35], humans [10] and bats [18].…”
Section: Discussionsupporting
confidence: 90%
“…Using the thymidine kinase obliteration system, Borrelli et al [3] reported that both GH cells and PRL cells derive from a common GH-expressing stem GH cell, which terminally differentiates into GH and PRL cell populations in transgenic mice. These findings support a possible transformation of GH cells into PRL cells, with MS cells acting as an intermediate cell in swine adenohypophysis as previously described in the adenohypophysis of rats [5,13,26,35], humans [10] and bats [18].…”
Section: Discussionsupporting
confidence: 90%
“…Nevertheless, it is possible that maturational changes in neuropeptide release or in the somatotroph responsiveness to somatostatin, growth hormone-releasing hormone (GHRH) and ghrelin might contribute to the pattern of circulating GH levels. Although data regarding gender differences in hypothalamic and somatostatin content are conflicting (17), it has been shown that in vitro GH responses to GHRH are influenced by age and gonadal status (18). Although no data are currently available regarding the influence of gonadal function on in vitro GH responses to ghrelin, it should be noted that GH responses to hexarelin are greater at the late postpubertal period (19).…”
Section: Discussionmentioning
confidence: 99%
“…Estrogen stimulates the proliferation of pituitary cells including PRL cells (Takahashi et al, 1984). Ho et al(1988) recently found by reverse hemolytic plaque assay that estrogen increased the number of GH cells, PRL cells, non-GH-and non-PRL-secreting cells. We had previously reported that long-term ovariectomy prevented the age-related increase in the number of PRL cells (Takahashi and Kawashima, 1983).…”
Section: Discussionmentioning
confidence: 99%